Implementation of Regional Financial Statements using Internet Financial Reporting - Hapsari, Dini Wahjoe; Juniantika, Dhita Aira; Manurung, Daniel T H; Rizal, Noviansyah (International Journal of Psychosocial Rehabilitation, 2020)
Internet Financial Reporting (IFR) is a way of delivering financial reports and capabilities in a multimedia manner by presenting interactive financial information, where disclosure of financial statements via the internet or website to the public is voluntary, open, easy and fast. IFR can provide the government in the distribution of financial information to various levels of society, stakeholders and investors. The research aims to analyze internal financial reporting as the delivery of government financial statements. The study used panel data regression and purposive sampling method with 65 samples from 13 official sites of regency/city governments in West Java Province in 2014 - 2018. The results of the study stated that local government wealth did not affect internet financial reporting, variable levels of government debt did not affect internet financial reporting, while audit opinion influences internet financial reporting.